INOVASI PEMBELAJARAN SKI MELALUI PEMANFAATAN PLATFORM DIGITAL - Sabrun Jamil; Hesti Rahmawati; Mutiara Haya Afifah; Aulya Putri; Yusuf Budiarto; Ridho Agustian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic Cultural History (SKI) education plays an important role in shaping students' historical understanding, Islamic values, and character. However, SKI education still faces various problems, such as monotonous teaching methods, limited learning media, low student interest and motivation, and difficulty in understanding chronological and conceptual material. With the development of technology, the use of digital platforms has become one of the innovative solutions to improve the quality of SKI learning. This study aims to examine innovations in SKI learning through the use of digital platforms and analyze the benefits and challenges in the learning process. The research method used is library research, by reviewing various sources such as books, scientific journals, and relevant literature related to SKI learning and educational technology. The results of the study show that the use of digital platforms such as audio-visual media, social media, e-learning, educational games, and artificial intelligence-based technology can increase students' interest, motivation, and understanding of SKI material. Learning becomes more interactive, contextual, and encourages active student participation. In addition, digital platforms also help teachers deliver material more effectively and efficiently. Thus, digital platform-based SKI learning innovation can be a strategic alternative in responding to the challenges of SKI learning in the digital era, while supporting the achievement of Islamic education goals oriented towards character building and digital literacy of students.